Strategic management and business growth: a bibliometric analysis - Petronella George; Suddin Lada; Faerozh Madli; Ang, Hong Loong; Umi Wahidah (Penerbit UMS, 2022)
Numerous scope of strategic management has captured scholars’ engagement. It is the set of approaches that contribute significantly to business performance and growth. In this study, there are three constructed research objectives; identifying the popular keywords, the publisher that publishes a high volume of articles and determining the journal that produces the most of the population sample. We conduct a PRISMA-guided systematic review and extracted data from an Excel Spreadsheet based on Scopus databases in the context of strategic management by focusing on the context of business growth of published articles from 2013 to 2022. As a result, as many as 2841 articles are obtained before any filtration on May 2022. In addition, the current study also found 264 articles as our final sample population after filtering the eligibility criteria such as year of publications, language and subject area. Our results show a rapid increase in the number of studies in the past three and four-year periods and most of the papers have been published in the United States, the remaining are in other countries such as the United Kingdom, America and Russia. This study also has indirectly delivered a good impact on the other researchers, which assist them not only in regards to systematic review but also the other methods that probably could implement in the related topic of study. In addition, the current study suggests that future research investigates strategic management positions in any industry and journals probably by using qualitative and quantitative research approaches.